(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the linguistic and cognitive features of metaphorical thinking and the system of images in Muhiddin Omon’s works. It examines the mechanisms of metaphor formation, nationalcultural concepts, and the imagery shaped through these concepts in the poet’s literary texts. The study explains the semantic fields of metaphorical units, the nature of conceptual metaphors, and their role in constructing poetic meaning within the framework of cognitive linguistics. The research also identifies the national and individual poetic manifestations of metaphorical thinking in Muhiddin Omon’s poetics